Numerical and statistical analyses of a natural convection radiative hybrid nanofluid flow on a vertical permeable plate - Wahid, Nur Syahirah; Mustafa, Mohd Shafie; Arifin, Norihan M. D.; Khashi’ie, Najiyah Safwa; Pop, Ioan (National Library of Serbia, 2024)
This study presents the mathematical and statistical findings towards the model of steady, laminar, natural convection hybrid Al2O3-Cu/water nanofluid flow on a vertical permeable hot plate with a thermal radiation effect. The governing PDE of the model are simplified to a system of ODE by using the sophisticated similarity transformation. For mathematical analysis, a finite difference method is used via the numerical solver known as bvp4c (MATLAB) while for statistical analysis, a response surface methodology is adapted via MINITAB. It is found that the stronger thermal radiation effect improves the heat transmission rate of the hybrid nanofluid under the presence of suction and natural convection. This finding has been statistically proven through the optimization technique via response surface methodology with 99.97% desirability.